108k views
2 votes
Prove by mathematical induction that


cos\theta+cos3\theta+cos5\theta+...+cos(2n-1)\theta=(sin2n\theta)/(2sin\theta)
where sinθ≠0 for all positive integers n.

1 Answer

1 vote

For
n=1, on the left we have
\cos\theta, and on the right,


(\sin2\theta)/(2\sin\theta)=(2\sin\theta\cos\theta)/(2\sin\theta)=\cos\theta

(where we use the double angle identity:
\sin2\theta=2\sin\theta\cos\theta)

Suppose the relation holds for
n=k:


\displaystyle\sum_(n=1)^k\cos(2n-1)\theta=(\sin2k\theta)/(2\sin\theta)

Then for
n=k+1, the left side is


\displaystyle\sum_(n=1)^(k+1)\cos(2n-1)\theta=\sum_(n=1)^k\cos(2n-1)\theta+\cos(2k+1)\theta=(\sin2k\theta)/(2\sin\theta)+\cos(2k+1)\theta

So we want to show that


(\sin2k\theta)/(2\sin\theta)+\cos(2k+1)\theta=(\sin(2k+2)\theta)/(2\sin\theta)

On the left side, we can combine the fractions:


(\sin2k\theta+2\sin\theta\cos(2k+1)\theta)/(2\sin\theta)

Recall that


\cos(x+y)=\cos x\cos y-\sin x\sin y

so that we can write


(\sin2k\theta+2\sin\theta(\cos2k\theta\cos\theta-\sin2k\theta\sin\theta))/(2\sin\theta)


=(\sin2k\theta+\sin2\theta\cos2k\theta-2\sin2k\theta\sin^2\theta)/(2\sin\theta)


=(\sin2k\theta(1-2\sin^2\theta)+\sin2\theta\cos2k\theta)/(2\sin\theta)


=(\sin2k\theta\cos2\theta+\sin2\theta\cos2k\theta)/(2\sin\theta)

(another double angle identity:
\cos2\theta=\cos^2\theta-\sin^2\theta=1-2\sin^2\theta)

Then recall that


\sin(x+y)=\sin x\cos y+\sin y\cos x

which lets us consolidate the numerator to get what we wanted:


=(\sin(2k+2)\theta)/(2\sin\theta)

and the identity is established.

User Cosmin Atanasiu
by
5.1k points